Workshop Metode Pengajaran Al-Qur'an dengan Bantuan Komputer (Computer Assisted Learning) - Salam, Abdus; Ihsanuddin, Ihsanuddin; Imilda, Imilda; Hajriyanti, Rahmi; Zahra, Rita; Ismail, Ismail (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2025)
The rapid development of information and communication technology has had a significant impact on various sectors, including education. The integration of technology in Quranic education offers great potential to enhance the quality of learning. This study aims to develop a workshop focusing on the implementation of the Computer Assisted Learning (CAL) method in Quranic instruction. The workshop is designed to equip educators with technical skills in utilizing educational technology, such as interactive tajwid simulators, audio tools, and automatic evaluation systems. Research indicates that the use of technology can significantly improve student motivation and the effectiveness of Quranic education. Akrami (2024) found that mobile-based applications effectively enhance student learning outcomes, while Hakimi (2024) emphasized the importance of flexible and interactive approaches in teaching. Through this workshop, educators are expected to apply technology effectively within Quranic curricula, thereby improving teaching quality and enriching students' learning experiences.